Mycobacterium leprae DNA in peripheral blood may indicate a bacilli migration route and high‐risk for leprosy onset. (28th August 2013) - Reis, E. M.; Araujo, S.; Lobato, J.; Neves, A. F.; Costa, A. V.; Gonçalves, M. A.; Goulart, L. R.; Goulart, I. M. B.; Bottieau, E.
Abstract Leprosy epidemiological studies have been restricted to Mycobacterium leprae DNA detection in nasal and oral mucosa samples with scarce literature on peripheral blood. We present the largest study applying quantitative real‐time PCR (qPCR) for the detection of M. leprae DNA in peripheral blood samples of 200 untreated leprosy patients and 826 household contacts, with results associated with clinical and laboratory parameters. To detect M. leprae DNA a TaqMan qPCR assay targeting the M. leprae ML0024 genomic region was performed. The ML0024 qPCR in blood samples detected the presence of bacillus DNA in 22.0% (44/200) of the leprosy patients: 23.2% (16/69) in paucibacillary (PB), and 21.4% (28/131) in multibacillary (MB) patients. Overall positivity among contacts was 1.2% (10/826), with similar percentages regardless of whether the index case was PB or MB. After a follow‐up period of 7 years, 26 contacts have developed leprosy. Comparing the results of healthy contacts with those that become ill, ML0024 qPCR positivity at the time of diagnosis of their index case represented an impressive 14.78‐fold greater risk for leprosy onset (95% CI 3.6–60.8; p <0.0001). In brief, contacts with positive PCR in blood at diagnosis of index cases are at higher risk of later leprosy onset and this marker might be combined with other prognostic markers for management of contacts, which requires further studies.